Réponses

2014-01-26T23:08:47+01:00
Bonsoir,

1) 6x² - 15x = 0
3x(2x - 5) = 0
3x = 0   ou   2x - 5 = 0
x = 0/3   ou   2x = 5
x = 0   ou   x = 5/2

2) 4x² -1 = 0 
(2x + 1)(2x - 1) = 0
2x + 1 = 0   ou   2x - 1 = 0
2x = -1   ou   2x = 1
x = -1/2   ou   x = 1/2


3) x² - 2 = 0
(x + V2)(x - V2) = 0
x + V2 = 0   ou   x - V2 = 0
x = -V2   ou  x = V2


4) (3x - 2)² = 1
(3x - 2)² - 1 = 0
[(3x - 2) + 1][(3x - 2) - 1] = 0
(3x - 2 + 1)(3x - 2 - 1) = 0
(3x - 1)(3x - 3) = 0
3x - 1 = 0   ou  3x - 3 = 0
3x = 1   ou   3x = 3
x = 1/3   ou   x = 3/3
x = 1/3   ou   x = 1